Evaluación de Beauveria Bassiana a partir de un cultivo monospórico para el control de gallina ciega (Phyllophaga spp), en condiciones de laboratorio campus Salache, Latacunga, Cotopaxi 2022. - Azogue Gavilanez, Wellington David (2022)
Among the most important pests of corn cultivation is the blind hen (Phyllophaga spp.), being an insect that causes damage to the roots, causing the death of up to 50% of the plants in the first phase of growth. The purpose of the research was to determine the best concentration of Beauveria bassiana and identify the best substrate for the behavior of the fungus, proposed a method of biological control for the insect. The present research was carried out in the Agronomy Laboratory of the Technical University of Cotopaxi, a completely random block design (DBCA) was used with a factorial arrangement of A x B + 1 additional with seven treatments and four repetitions, where the factors under study were; Factor A concentrations of Beauveria bassiana (108, 109, 1010 conidia/ml) and Factor B (sterilized and unsterilized substrate) obtaining a total of 28 experimental units with 10 larvae of (Phyllophaga spp.) for each experimental unit. The variables determined were percentage of mortality and concentration of conidia/ml 108, 109, 1010. The results obtained by means of an ADEVA were the treatments, concentrations and interactions of factors A and B that gave highly significant, in which Tukey tests were proposed at 5% to determine which treatment is rebound, the analysis of Factor B was not significant. The result for the percentage of mortality was determined in treatment six (T6) that corresponds to the application of Beauveria bassiana with a concentration of 1010 conidia / ml in the unsterilized substrate, reaching 95% mortality, being the best compared to the additional one that did not present dead larvae. Therefore it is concluded that the best concentration was 1010 conidia/ML in unsterilized soil.